Association Between the IL-6 rs1800795 Polymorphism and the Risk of Cervical Cancer: A Meta-Analysis of 1210 Cases and 1525 Controls. (October 2017) - Liu, Haiping; Lyu, Dan; Zhang, Yan; Sheng, Lianbing; Tang, Ning
Cervical cancer is the second most common cancer and the third leading cause of cancer-related death among females in less developed countries. Studies have shown that the single-nucleotide polymorphisms of interleukin 6 might be associated with cervical cancer risk. A total of 710 articles from EMBASE, EBSCO, Web of science, PubMed, Springer link, and Chinese National Knowledge Infrastructure databases were reviewed in our study. A meta-analysis on the associations between interleukin 6 rs1800795 polymorphism and cervical cancer risk was carried out by comparison using 5 genetic models. In this systematic review, 5 studies were analyzed. The pooled population included 2735 participants (1210 cases and 1525 controls). The overall odds ratio (G vs C alleles) using fixed-effects model was 0.85 (95% confidence interval 0.75-0.97), P = .02. Our results show that the C genotype of interleukin 6 rs1800795 is associated with higher cervical cancer risk. Our results indicate that interleukin 6 rs1800795 polymorphism might be associated with susceptibility to cervical cancer.